SOCIOLOGICAL ANALYSIS OF YOUTH INTERNET-COMMUNITY FUNCTIONING - Andrey Grigorevich Plisyuk (Вестник Северо-Кавказского федерального университета)
The article provides a view on the methodological issues of scientific research into Internet-communities. There is an outline of the results of the sociological research focusing at the functional features about youth Internet-communities. There is also an analysis of a social image of a typical user in the nowadays Internet-community.